Serum markers of neuroinflammation and oxidative stress in modeling spinal injury of various genesis - D. I. Pozdnyakov; V. V. Kozlova; V. F. Reps (Сеченовский вестник)
Aim. To evaluate changes in the concentration of molecules that mark the neurodegenerative process, experimental spinal cord injuries (SCI) of various origins were studied.Materials and methods. SCI was modeled in six-month-old male Wistar rats by exposing the T10 vertebra to: carbon dioxide under a pressure of 2 N/cm2 (pneumocontusion); free-falling load of three weights of 1.12 N/cm2, 1.68 N/cm2, 1.96 N/cm2 (contusion injury); compression with forceps (compression injury); partial hemisection of the spinal cord; mechanical laminectomy using a mechanical drill. There were 6 rats in each group, including the intact control group. On the 28th day after a single application of SCI in rats, the concentrations of tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL-6), albumin, thiobarbituric acid reactive substances (TBA-RS) and superoxide dismutase activity were assessed in the blood serum.Results. When modeling SCI of various origins in rats, the serum concentration of TNF-α increased (from 115.5% (p < 0.05) in mild contusion to 234.5% (p < 0.05) in compression trauma compared to intact control) as well as IL-6 (from 49.2% (p < 0.05) in mechanical laminectomy to 89.8% (p < 0.05) in hemisection compared with intact control), suggesting activation of inflammatory reactions. The concentration of albumin in the blood serum of rats with SCI was lower than that of intact animals, especially in the hemisection group – by 41.9% (p < 0.05). Animals with SCI had an increase in TBA-RS concentration ranging from 103.2% (p < 0.05) in mild contusion and compression to 135.5% (p < 0.05) in pneumocontusion, and a decrease in superoxide dismutase activity ranging from 26.3% (p < 0.05) in laminectomy to 31.7% (p < 0.05) in hemisection. At the same time, injuries caused by spinal compression and hemisection led to a more pronounced activation of the inflammatory process, as evidenced by the increased TNF-α content compared to other variants of SCI modeling.Conclusion. All SCI simulations resulted in equivalent activation of oxidative stress, while inflammation is more pronounced when reproducing compression injury and injury caused by spinal hemisection.